Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide - Dapurkar, Sudhir E.; Kawanami, Hajime; Chatterjee, Maya; Rode, Chandrasekhar V.; Yokoyama, Toshirou; Ikushima, Yutaka (Applied Catalysis A-General, 2011)
Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide (scCO(2)) has been investigated. The catalyst used was a chromium containing mesoporous molecular sieve catalyst viz. CrMCM-41. Comparison studies were performed with CoMCM-41. PtMCM-41 and PdMCM-41 catalysts. Among the various catalysts studied. CrMCM-41 showed a high conversion of geraniol and an excellent selectivity for citral. In contrast CoMCM-41, PtMCM-41 and PdMCM-41 catalysts exhibited low conversion of geraniol. However all three catalysts compared showed similar citral selectivity to CrMCM-41. The effect of CO(2) pressure and reaction temperature geraniol oxidation was studied with CrMCM-41. Supercritical CO(2) medium was found to enhance the conversion of geraniol and/or yield of citral. It was noticed that the catalyst can be recycled with negligible loss of conversion. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Citral; Geraniol; heterogeneous catalyst; Molecular oxygen; Selective oxidation; Supercritical carbon dioxide

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Heterogeneous Co3O4 catalyst for selective oxidation of aqueous veratryl alcohol using molecular oxygen - Mate, Vivek R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Catalysis Communications, 2013)
Nano-structured, spinel Co3O4 catalyst was developed for the aqueous phase oxidation of veratryl alcohol, which showed the highest conversion of 85% with 96% selectivity to veratryl aldehyde. The co-existence of Co3+ and Co2+ species in the octahedral and tetrahedral positions respectively, was confirmed by XPS, cyclic voltammogram, TPR and TPO characterization. The rod-like morphology of Co3O4 catalyst was confirmed by HRTEM. The effects of various reaction parameters namely, catalyst concentration, temperature and partial oxygen pressure on conversion and selectivity patterns were also studied for the oxidation of veratryl alcohol. This catalyst also showed an excellent stability as evidenced by successful reusability for three times. (C) 2012 Published by Elsevier B.V.
Keywords: Co3O4; Cyclic voltammogram; Liquid phase oxidation; Molecular oxygen; Veratryl alcohol; XPS